Developing a ranking methodology for ' Sharīʿah indices: The case of Borsa Istanbul - Zeyneb Hafsa Orhan; Murat Isiker (ISRA International Journal of Islamic Finance, 2021)
Purpose - This paper aims to develop a ranking methodology for the companies included in the Islamic indices in Turkey. Thus, this paper simplifies the decision-making process for investors with Islamic sensitivities to stock market investment when constructing their investment portfolio. Design/methodology/approach - This paper uses a case study of 20 companies listed on Borsa Istanbul, drawing data from their 2017, 2018 and 2019 financial reports. These companies are scored and ranked according to their compatibility with the screening criteria used by Ziraat Katilim index in Turkey. In addition, this paper uses the quantitative screening process to calculate the ranking scores of these companies. Findings - The findings show that some companies are highly compatible with the screening criteria, with ranking scores close to 100 points. However, some companies satisfied the criteria on the margin. This may not be a desirable result for some investors. Research limitations/implications - Only 20 companies are included in the analysis. Since the conventional accounting system is used in Turkey, it was difficult to get exact information about the companies' Sharīʿah compatibility from the financial results. Practical implications - The findings assist investors to determine which company is ethically more responsible than others within the Islamic framework. There are also implications for the companies in question, index providers and Sharīʿah scholars. Social implications - The findings aim to simplify the decision-making process of investors who have Islamic sensitivities to stock exchange market investment when they constitute their portfolio. Originality/value - To the best of the authors' knowledge, it is one of the first attempts to develop a ranking methodology for Sharīʿah-screened stocks in Turkey even though Sharīʿah screening has been on the agenda since the late 1990s. This paper also compares 11 indices based on their screening criteria.
Keywords: 330; Borsa Istanbul; Islamic capital markets; Ranking methodology; Sharīʿah-compliant investment; Ziraat Katılım index